Bangladesh Rural Advancement Committee (BRAC): organizational innovation in population, health and development in Bangladesh in the context of the millennium development goals - Haider, Muhiuddin (BRAC University, 2010)
Bangladesh has marked strides to make in reaching the Millennium Development Goals (MDGs)for child mortality and maternal health by 2015. Progress and achievements that have been made to date are recognized. However, challenges remain that may impede steady progress towards the realization of the goals, including social inequality, largely defined by the low status of women, and the rich-poor divide. BRAC’s innovative organizational approach in Bangladesh serves to fill in the gaps left by the public sector, and brings a comprehensive approach to addressing these challenges and encouraging advances in health and development.